2014
DOI: 10.1007/s00125-014-3327-4
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus RNA in longitudinal blood samples and risk of islet autoimmunity in children with a high genetic risk of type 1 diabetes: the MIDIA study

Abstract: Positivity for enterovirus RNA in blood did not predict the later induction of islet autoantibodies, but enterovirus tended to be detected more often at the islet autoantibody seroconversion stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…The excess of infections preceded the appearance of autoantibodies, paralleling the findings from our previous prospective studies in the DIPP study, the Trial to Reduce IDDM in the Genetically at Risk (TRIGR) pilot and the Childhood Diabetes in Finland (DiMe) cohorts, in which enterovirus infections were documented by antibody assays and detection of viral RNA from serum [6,9,11,[24][25][26]. In addition, the Norwegian Environmental Triggers of Type 1 Diabetes (MIDIA) study also observed a peak in enterovirus RNA in blood at the time of autoantibody seroconversion [12]. Altogether, these findings suggest that enterovirus infections might play a role in the initiation of the beta cell-damaging process.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The excess of infections preceded the appearance of autoantibodies, paralleling the findings from our previous prospective studies in the DIPP study, the Trial to Reduce IDDM in the Genetically at Risk (TRIGR) pilot and the Childhood Diabetes in Finland (DiMe) cohorts, in which enterovirus infections were documented by antibody assays and detection of viral RNA from serum [6,9,11,[24][25][26]. In addition, the Norwegian Environmental Triggers of Type 1 Diabetes (MIDIA) study also observed a peak in enterovirus RNA in blood at the time of autoantibody seroconversion [12]. Altogether, these findings suggest that enterovirus infections might play a role in the initiation of the beta cell-damaging process.…”
Section: Discussionsupporting
confidence: 82%
“…The results from such studies have suggested that enterovirus infections, diagnosed by serology or by direct detection of the virus from blood, are associated with the appearance of islet autoantibodies long before clinical diabetes is diagnosed [6,9,11,12]. In contrast, the detection of the virus in stools has not shown such an association [13,14], and in one study in which both blood and rectal swabs were analysed, no association at all was found [15].…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have tried to address this hypothesis by serological, immunohistological, and molecular methods (12,13). However, a direct one-on-one relationship of a viral strain only present in patients with T1D has never been found-the reason could be that viruses trigger diabetes as a hit-and-run event and therefore their traces are often not detectable.…”
mentioning
confidence: 99%
“…One of the most important future tasks is to confirm the risk association between EV infections and T1D in different populations. In addition to the DIPP study this risk association has been found in other prospective studies in Finland and in one study from Norway . However, prospective studies which would have been large enough to evaluate the role of EVs in the initiation of islet autoimmunity with satisfactory statistical power are not available from other countries, and such studies should be carried out to confirm this association in different populations.…”
Section: Discussionmentioning
confidence: 58%